2012
DOI: 10.1038/onc.2012.467
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil signaling through a calcium–calmodulin-dependent pathway is required for p53 activation and apoptosis in colon carcinoma cells

Abstract: 5-Fluorouracil (5-FU) is an anti-metabolite that is in clinical use for treatment of several cancers. In cells, it is converted into three distinct fluoro-based nucleotide analogs, which interfere with DNA synthesis and repair, leading to genome impairment and, eventually, apoptotic cell death. Current knowledge states that in certain cell types, 5-FU-induced stress is signaling through a p53-dependent induction of tumor necrosis factor-receptor oligomerization required for death-inducing signaling complex for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 40 publications
(54 reference statements)
3
32
0
Order By: Relevance
“…In HCT116 cells exposed to high-dose 5-FU, DR5 and FAS were previously shown to translocate to the plasma membrane, and DR5 silencing impeded caspase activation (Can et al, 2013). To assess the involvement of DR5, FAS and DR4 (another death receptor) in synthetic lethality, we silenced expression of each with small interfering RNA (siRNA), treated cells with 3-MB-PP1 and either 5-FU or nutlin-3, and measured markers of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…In HCT116 cells exposed to high-dose 5-FU, DR5 and FAS were previously shown to translocate to the plasma membrane, and DR5 silencing impeded caspase activation (Can et al, 2013). To assess the involvement of DR5, FAS and DR4 (another death receptor) in synthetic lethality, we silenced expression of each with small interfering RNA (siRNA), treated cells with 3-MB-PP1 and either 5-FU or nutlin-3, and measured markers of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have described changes in different cancer cell types and models in intracellular Ca 2+ signals induced by some anti-cancer agents. Drug treatments that appeared to increase Ca 2+ influx as a result of short-term (0 to 8 h) exposure included 5-Fluorouracil (5FU) (Can et al 2013), dexamethasone (Abdul-Azize et al 2017), Tipifarnib (Cuevas 2011;Yanamandra et al 2011) or ionizing radiation (Klumpp et al 2016). Drugs such as arsenic trioxide (As 2 O 3 ) (Gunes et al 2009) and gamitrinib (Park et al 2014) were suggested to promote ER Ca 2+ release during short-term exposure.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose continuous treatment with 5-FU causes DNA damage in proliferating cells through inhibition of thymidylate synthase, a key component of DNA synthesis and repair pathways. In addition to tumors, HP and GI cells demonstrate 5-FU sensitivity [22, 23]. Hematological toxicity of 5-FU involves p53-mediated induction of ribosomal stress, which blocks translation [24, 25].…”
Section: Introductionmentioning
confidence: 99%